Effectiveness of early warning and community cooperation for evacuation preparedness from mega-risk type coastal hazard in childcare centers. Issue 4 (29th August 2019) - Pinheiro, Abel Táiti Konno; Hokugo, Akihiko
Abstract : Purpose: This paper aims to investigate the effectiveness of early warning and community cooperation for evacuation preparedness from mega-risk type coastal hazard in childcare centers, focusing in the evacuation of childcare centers from tsunami at the time of the Great East Japan Earthquake occurred on March 11, 2011. Design/methodology/approach: As the research method, surveys were conducted in public childcare centers affected by tsunami in Kesennuma city in Miyagi Prefecture and Kamaishi city in Iwate Prefecture. Findings: As the main findings, facilities, where teachers and children started evacuation immediately after the earthquake, could have more conditions to get cooperation from the local community to evacuate children in wide-scale urban environment. Children 3-5 years old tended to be instructed to walk two abreast under the lead of teachers, and children 0-2 years old tended to be carried by the piggyback ride and multi-passenger baby strollers. The destination of evacuation needed to be changed several times because of the risks for higher tsunami and fire outbreaks. Research limitations/implications: As future issues, it is necessary to analyze the walking capability of children and the transportation capability of multi-passenger baby strollers by teachers, to address strategies to quantify the necessary community cooperation based on the severity of early warning. Originality/value: Most of the past studies regarding disaster preparedness of nursery children are limited within the facility in case of fire. This work has importance as it focused on the emergency responses that require urban-scale evacuation in ascending route that differ from that which are required in the case of fire.